The Effect of Motor Skill Training Program on Activity of Daily Living in Children with Developmental Coordination Disorder - Sabiilaa, Syauqinaa; Hariandja, Andy M.A.; Laksono, Abdurahman B.B. (Poltekkes Kemenkes Jakarta III, 2022)
The incidence of children with developmental coordination disorder (DCD) is about 5% to 6% in school-age with 1.7 to 2.8 times more likely to occur in boys than girls. Difficulties in all motor activities, including activities daily living (ADL) are experienced by children with DCD. Motor skill training (MST) which a task-oriented based on basic motor abilities is highly recommended to improve motor achievement and execution of specific motor functions in children with DCD. The purpose of this study was to determine the effect of MST in increasing ADL ability in children with DCD. This research used pre-experimental study with 'the one group pretest-posttest design'. Ten children were selected as respondents to observe their ADL ability using DCDDaily before and after being given MST. The result of statistical analysis showed significant change in the total ADL score before and after being given MST (mean difference 13.95, p-value 0.001), with mean difference of total score before and after 15.9 (p-value 0.001) and mean difference of total score quality before and after 8.4 (p-value 0.005). The conclusion of this research is motor skill training can help improve ADL abilities in children with DCD.